Analisis Tradisi Sastra Lisan Nyumber di Desa Dermaji Kecamatan Lumbir Kabupaten Banyumas Kajian Antropologi Sastra - Dwi Setiyawan (Journal on Education, 2021)
This analysis aims to determine the Nyumber oral literary tradition in Dermaji village, Lumbir District, Banyumas Regency, Central Java. This analysis uses a literary anthropology approach. The data collection technique was carried out by interviews. After conducting interviews, it was found that Nyumber had several offering components that had to be fulfilled. The values ​​contained in it are social, religious and cultural values. Nyumber is an expression of gratitude to God for the construction of a house or building. People believe that if they don't do it, bad things will happen. Nyumber is one of the traditions in which there are patterns of Hinduism and Islam. Hinduism can be seen from the presence of offerings in the process and Islam can be seen from the group prayer event after the burial procession of offerings.